Forced turbulence in thermally bistable gas: a parameter study - Seifried, Daniel; Schmidt, Wolfram; Niemeyer, Jens (Astronomy and astrophysics, 2011)
Context. Thermal instability is one of the dynamical agents for turbulence in the diffuse interstellar medium, where both turbulence and thermal instability interact in a highly non-linear manner. Aims. We study basic properties of turbulence in thermally bistable gas for variable simulation parameters. The resulting cold gas fractions can be applied as parameterisation in simulations on galactic scales. Methods. Turbulent flow is induced on large scales by means of compressive stochastic forcing in a periodic box. The compressible Euler equations with constant UV heating and a parameterised cooling function are solved on uniform grids. We investigate several values of the mean density of the gas and different magnitudes of the forcing. For comparison with other numerical studies, solenoidal forcing is applied as well. Results. After a transient phase, we observe that a state of statistically stationary turbulence is approached. Compressive forcing generally produces a two-phase medium, with a decreasing fraction of cold gas for increasing forcing strength. This behaviour can be explained on the basis of turbulent mixing. We also find power-law tails of probability density functions of the gas density in high-resolution runs. Solenoidal forcing, on the other hand, appears to prevent the evolution into a two-phase-medium for certain parameter regions. Conclusions. The dynamics of thermally bistable turbulence show a substantial sensitivity to the initial state and the forcing properties.